PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA (KDRT) MELALUI KONSEP HAK DAN KEWAJIBAN SUAMI ISTERI DALAM ISLAM - Muslim, Muslim (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2019)
Domestic violence is a disease in people's lives and is the responsibility of the government to handle it. The PKDRT Law was issued to deal with domestic violence issues, but in reality the PKDRT Law has not been able to resolve this problem completely. What is the cause of domestic violence in the community is apparently caused by the character of the community and this character is strongly influenced by the perception of husband and wife about the rights and obligations of husband and wife in navigating the household. The cause of domestic violence is more because they feel each party feels they have rights that must be fulfilled by the other party, while the other party may feel it is not their obligation. This happens because in understanding rights and obligations there is diversity so that it causes disagreement that can lead to disputes and violence. Religion is a guide to human life, about the rights and obligations of husband and wife already have concepts in fiqh